Absolute Tauberian Constants for Lower Triangular Matrices - Akgun, F. Aydin; Rhoades, B. E. (Sarajevo Journal of Mathematics, 2024)
In a recent paper [1] the authors obtained absolute Tauberian constants for the H-J generalized Hausdorff transformations, which generalized the corresponding results, obtained earlier by Sherif, for ordinary Hausdorff matrices. In this paper we obtain absolute Tauberian constants for regular lower triangular matrices with row sums one. As corollaries we obtain the corresponding results for factorable and weighted mean matrices. 2010 Mathematics Subject Classification. Primary: 47H10.